An anti-G protein monoclonal antibody treats RSV disease more effectively than an anti-F monoclonal antibody in BALB/c mice - Boyoglu-Barnum, Seyhan (Virology, 2015)
Respiratory syncytial virus (RSV) belongs to the family Paramyxoviridae and is the single most important cause of serious lower respiratory tract infections in young children, yet no highly effective treatment or vaccine is available. To clarify the potential for an anti-G mAb, 131-2G which has both anti-viral and anti-inflammatory effects, to effectively treat RSV disease, we determined the kinetics of its effect compared to the effect of the anti-F mAb, 143-6C on disease in mice. Treatment administered three days after RSV rA2-line19F (r19F) infection showed 131-2G decreased breathing effort, pulmonary mucin levels, weight loss, and pulmonary inflammation earlier and more effectively than treatment with mAb 143-6C. Both mAbs stopped lung virus replication at day 5 post-infection. These data show that, in mice, anti-G protein mAb is superior to treating disease during RSV infection than an anti-F protein mAb similar to Palivizumab. This combination of anti-viral and anti-inflammatory activity makes 131-2G a promising candidate for treating for active human RSV infection.